Numerical investigation of models for drag, lift, wall lubrication and turbulent dispersion forces for the simulation of gas-liquid two-phase flow - Yamoah, S.; Martínez-Cuenca, R.; Monrós, G.; Chiva, S.; Macián-Juan, R. (Chemical Engineering Research and Design, 2015)
In order to qualify CFD codes for accurate numerical predictions of transient evolution of flow regimes in a vertical gas-liquid two-phase flow in a pipe, suitable closure models (inter-phase forces) for the momentum exchange between the continuous and dispersed phases are needed. In this study, under the assumption of monodisperse bubbles, a consistent set of inter-phase force models have been investigated. The effect of Drag Force, Lift Force, Wall Lubrication Force and Turbulent Dispersion Force has been assessed. The predicted local radial distributions of four primitive variables: gas volume fraction, interfacial area concentration, gas velocity and liquid velocity, are validated against experimental data of Monrós-Andreu et al. (2013, EPJ Web Conf. 45, 01105). New parameters have been introduced in the wall lubrication force models of Antal et al. (1991, Int. J. Multiphase Flow 7, 635) and Frank et al., (2004, Proc. of the Third Int. Symposium on Two-Phase Modelling and Experimentation, Pisa, Italy, 2008, Nucl. Eng. and Des. 238, 647) as well as implementing additional drag coefficient models using CFX expression language (CEL). In general, the predictions from the sets of inter-phase closure models presented in this paper yielded satisfactory agreement with the experimental results. Based on the result of the validation of different inter-phase force models, a set of Grace drag coefficient model, Tomiyama lift coefficient model, Antal et al.'s wall force model, and Favre averaged turbulent dispersion force was found to provide the best agreement with the experimental data. © 2015 The Institution of Chemical Engineers.
Keywords: Bubble flow; CFD; Gas-liquid flow; Simulation; Two-phase flow; Vertical pipe flow